Physiological demands and performance predictors of olympic ski mountaineering - Fornasiero, A.; Savoldelli, A.; Mattivi, M.; Forrer, T.; Todesco, B.; Cuniberti, G.; Callovini, A.; Schena, F.; Holmberg, H.-C.; Pellegrini, B.; Bortolan, L. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: The 2026 Milano-Cortina Winter Olympics will mark the debut of ski mountaineering, featuring two distinct competition formats: the Sprint and the Mixed-Relay. To date, the physiological demands and the predictors of performance in these ski mountaineering disciplines remain largely unexplored [1,2]. The purpose of this study was to investigate the physiological demand and the predictors of performance in the two Olympic formats.